Descriptive Analysis of Students' CGPA: A Case Study of Universiti Malaysia Pahang - Roslinazairimah, Zakaria; Siti Zanariah, Satari; N. A., Damahuri; Rozieana, Khairuddin (IOP Publishing, 2019)
This study presents the descriptive analysis of students’ performance based on the cumulative grade point average (CGPA) of the entry grade and the CGPA achieved throughout their study duration until graduation. The data analysed are students from all bachelor degree programme at Universiti Malaysia Pahang of 2011, 2012 and 2013 cohorts. Components related to academic performance such as gender, entry qualification, CGPA (entry, all semesters), academic programme and cohort are analysed using the descriptive statistics. The results show that students from Sijil Tinggi Pelajaran Malaysia (STPM) performs very well academically with mean CGPA of 3.30 throughout the study period as compared to students from diploma (CGPA:2.97), matriculation (CGPA:2.88) or Sijil Tinggi Agama Malaysia (STAM; CGPA:2.71). The findings of the study can be used by the university’s administration to review intake policies and plan for the intervention program which could help improve the students’ academic performance.